Meta Analisis terhadap Peran Kepala Sekolah sebagai Pemimpin Perubahan - Putriana Kusuma Wardani; Teguh Triwiyanto (JMiE (Journal of Management in Education), 2022)
This study aims to determine the leadership role of the principal in changes in the school organization. This research uses a qualitative approach with a meta-analysis method which is carried out by analyzing data obtained from several previously existing studies. The results of the data analysis show that the principal as a leader of change in the school organization has a very important role, namely: (1) building and growing awareness of all elements of the school regarding the urgency of change; (2) create and develop a vision, mission, goals, strategies, and policies for school change by including the participation of all elements of the school; (3) communicate the vision, mission, objectives, strategies, and policies to obtain improvements and feedback; (4) provide support, motivation, and empowerment of school resources for a smooth process of change; (5) planning and striving for the realization of short-term benefits of change; (6) consolidate all elements of the school to realize the success of school change; (7) demonstrate commitment and do what is said; (8) evaluate to determine the success rate of changes and improvements that need to be made; and (9) hold celebrations by giving awards (rewards) to all elements of the school.